2021
DOI: 10.1021/acsinfecdis.1c00083
|View full text |Cite
|
Sign up to set email alerts
|

Quinoline and Quinazoline Derivatives Inhibit Viral RNA Synthesis by SARS-CoV-2 RdRp

Abstract: Coronavirus disease 2019 (COVID-19) is a fatal respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The identification of potential drugs is urgently needed to control the pandemic. RNA dependent RNA polymerase (RdRp) is a conserved protein within RNA viruses and plays a crucial role in the viral life cycle, thus making it an attractive target for development of antiviral drugs. In this study, 101 quinoline and quinazoline derivatives were screened against SARS-CoV-2 RdRp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Among them, 6-72-2a surprisingly showed similar inhibition effect as Remdesivir ( Table S1 ). The lipophilic Boc-group may contribute to the activity and a similar result was discovered in our another research, in which the stability of the Boc-group was also demonstrated ( Zhao et al, 2021b ). The structures of these five compounds also suggest that chemical structure of 2-((1H-indol-3-yl)thio) acetamide is pivotal element for its capability against RdRp ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Among them, 6-72-2a surprisingly showed similar inhibition effect as Remdesivir ( Table S1 ). The lipophilic Boc-group may contribute to the activity and a similar result was discovered in our another research, in which the stability of the Boc-group was also demonstrated ( Zhao et al, 2021b ). The structures of these five compounds also suggest that chemical structure of 2-((1H-indol-3-yl)thio) acetamide is pivotal element for its capability against RdRp ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Molnupinavir is an orally available and efficacious ribonucleoside analog inhibitor of influenza viruses and, similarly to remdesivir, it has been repurposed against SARS-CoV-2 18 . However, the RdRp complex of coronavirus can excise erroneous mutagenic nucleotides incorporated into viral RNA, thus creating resistance to nucleotide analog drugs 19 , 20 . Consequently, non-nucleoside inhibitors could have more desirable mechanisms of action that would limit the development of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Three quinoline derivatives (I-13e, I-13h, and I-13i) ( Fig. 9 A) , which are previously reported to have significant activity against the influenza A virus RdRp, exhibit remarkable potency in inhibiting RNA synthesis by targeting SARS-CoV-2 RdRp and relatively low cytotoxicity in a cell-based assay, with therapeutic index (TI) (CC 50 /EC 50 ) values of 65, 34, and 20, respectively [118] . Among these three compounds, I-13e showed the most potent inhibition of RNA synthesis and bypasses viral exonuclease activity concerns common with nucleotide inhibitors, thus holding the potential of being a drug candidate for the treatment of SARS CoV-2.…”
Section: Inhibitors Of Rdrpmentioning
confidence: 99%